Robust stability analysis of a dc/dc buck converter under multiple parametric uncertainties - Sumsurooah, Sharmila; Odavic, Milijana; Bozhko, Serhiy; Boroyevich, D. (Institute of Electrical and Electronics Engineers, 2017)
Stability studies are a crucial part of the design of power electronic systems, especially for safety critical ap¬plications. Standard methods can guarantee stability under nominal conditions but do not take into account the multiple uncertainties that are inherent in the physical system or in the system model. These uncertainties, if unaccounted for, may lead to highly optimistic or even erroneous stability margins. The structured singular value-based method justifiably takes into account all possible uncertainties in the system. However, the application of the method to power electronic systems with multiple uncertainties is not widely discussed in the literature. This work presents practical approaches to applying the method in the robust stability analysis of such uncertain systems. Further, it reveals the significant impact of various types of parametric uncertainties on the reliability of stability assessments of power electronic systems. This is achieved by examining the robust stability margin of the dc/dc buck converter system, when it is subject to variations in system load, line resistance, operating temperature and uncertainties in the system model. The predictions are supported by time domain simulation and experimental results.